Association of novel biomarkers of systemic inflammation with atherosclerosis and its severity - V. A. Shvarts; S. M. Talibova; M. A. Sokolskaya; A. Yu. Ispiryan; E. N. Shvarts; A. D. Petrosyan; V. Yu. Merzlyakov; A. I. Skopin; S. A. Donakanyan (Российский кардиологический журнал)
Aim. To compare the levels of novel biomarkers of systemic inflammation in patients with and without atherosclerosis, as well as between groups of patients with atherosclerosis of different severity.Material and methods. Patients with suspected coronary artery disease after selective coronary angiography were included. The analysis included 901 patients with mean age of 61±10 years (men, 60% (n=549)). The patients were divided into two following groups: with and without atherosclerosis. The Propensity Score Matching method was used to adjust for baseline clinical differences.Results. In the group with atherosclerosis, the values of the systemic inflammation response index (SIRI), systemic immune-inflammation index (SII) and aggregate index of systemic inflammation (AISI) were significantly higher than in patients without atherosclerosis: 0,906 (0,632; 1,36) vs 0,745 (0,519; 1,02), p<0,001; 457 (350; 641) vs 425 (313; 547), p=0,005 and 233 (148; 346) vs 179 (121; 263), p<0,001, respectively. ROC analysis showed the following threshold values of the studied parameters: for SIRI >1,05, area under the curve (AUC) confidence interval (CI) — 0,615 (0,571-0,658), p<0,001, sensitivity — 42,6%, specificity — 77,3%; for SII >368, AUC CI — 0,572 (0,528-0,616), p=0,004, sensitivity — 72,1%, specificity — 43,4%; for AISI >248, AUC CI — 0,604 (0,560-0,647), p<0,001, sensitivity 47,4%, specificity 71,1%. SIRI had the highest AUC. When comparing 6 groups according to the Coronary Artery Surgery Study (CASS) classification, significant differences were found in SIRI and AISI, p<0,001 and p=0,0016, respectively. However, these differences did not have a logical pattern.Conclusion. Novel markers of systemic inflammation (SIRI, SII and AISI) were significantly higher in patients with confirmed atherosclerosis than in patients without it. There are following threshold levels associated with atherosclerosis: for SIRI >1,05, for SII >368, for AISI >248.